Text-image Coupling for Editing Literary Sources. - Lecolinet, Eric; Robert, Laurent; Role, François (Computers & the Humanities, 2002)
Users need more sophisticated tools to handle the growing number of image-based documents available in databases. In this paper, we present a system devoted to the editing and browsing of complex literary hypermedia including original manuscript documents and other handwritten sources. Editing capabilities allow the user to transcribe manuscript images in an interactive way and to encode the resulting textual representation by means of a logical markup language (based on the XML/TEI specification). Both representations (image and structured text) are tightly linked to facilitate the reading and the interpretation of documents. This text/image coupling scheme is an attempt to unify several layers of information in order to provide the user with a global vision of the work. Our system also supplies tools capable of processing and relating information stored both in images and structured texts. Finally, application-specific visualization techniques have been developed in order to provide users with a way to identify relationships between source documents and help them to navigate.